Advances in Squeeze Casting Technique for Processing Discontinuous Ceramic Fibre Reinforced Metal Matrix Composite Materials - Vijayaram, Thoguluva Raghavan (INTI Publishing House Sdn. Bhd., 2006)
Squeeze casting is used for processing of ferrous, non-ferrous materials and metal matrix composites for different metals as well as alloy based matrices. The advantages of the squeeze casting method Include the minimization of porosity, pinhole and shrinkage defects, a 100 percent casting yield, an improved attainment of part details having complicated contours, a good surface finish, better dimensional accuracy, high strength to weight ratio, better wear resistance and corrosion resistance, improved hardness, better heat resistance, Improved fatigue and better creep strength. Hence engineering components manufactured using squeeze casting processes require fewer post machining operations.